Analysis of Factors Affecting The Maintenance Performance of Heavy Equipment in Construction Projects (Case Study In Morowali Project, Sulawesi) - Wahyu Widiarto; Sevtian Arief Nur Cahyo; Joko Nugroho; Darjat Sudrajat (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze various factors that affect the maintenance performance of heavy equipment in construction projects, with a focus on projects in Morowali, Sulawesi. Heavy equipment maintenance is a critical aspect that can affect the smooth and successful operation of a construction project. Through data collection using questionnaires distributed to workers and employees at the project site, this study evaluates the influence of work environment, employee competence, and spare parts availability on maintenance effectiveness. The results show that these factors have a significant impact on maintenance performance, which in turn affects the overall operation of the project. These findings are expected to provide insight for project managers in designing more effective maintenance strategies.